2016
DOI: 10.1186/s40104-016-0079-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thymol and carvacrol supplementation on intestinal integrity and immune responses of broiler chickens challenged with Clostridium perfringens

Abstract: BackgroundNecrotic enteritis caused by Clostridium perfringens infection leads to serious economic losses in the global poultry production. In the present study, we investigated the protective effects of essential oils (EO, which contained 25 % thymol and 25 % carvacrol as active components) supplementation on growth performance, gut lesions, intestinal morphology, and immune responses of the broiler chickens infected with C. perfringens. A total of 448 1-day-old male broiler chicks were allocated into eight t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
157
2
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(193 citation statements)
references
References 47 publications
20
157
2
14
Order By: Relevance
“…Although in some of these studies, the data did not indicate a clear positive effect of thyme on animal performance; it seems that the effects of thymol may depend on the diet formulation and the environment (Haselmeyer et al, ). However, other effects of thymol have been reported at intestinal levels such as intestinal injury by improving intestinal integrity and modulating immune responses in chickens infected with Clostridium perfringens (Du et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Although in some of these studies, the data did not indicate a clear positive effect of thyme on animal performance; it seems that the effects of thymol may depend on the diet formulation and the environment (Haselmeyer et al, ). However, other effects of thymol have been reported at intestinal levels such as intestinal injury by improving intestinal integrity and modulating immune responses in chickens infected with Clostridium perfringens (Du et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Reduced TJ integrity greatly increases ion conductance across the paracellular route resulting in a leaky gut, Tomita and Hayashi (). It was shown that broiler challenged with C. perfringens resulted in decrease of claudin‐1 and occludin gene expression and however disrupted the TJs between the epithelial cells Du et al (). Similarly, Li et al () discovered that C. perfringens challenged chickens decreased occludin mRNA expression in the jejunum.…”
Section: Discussionmentioning
confidence: 99%
“…During infection, the innate immune system of the host animal provides the first line of defense in pathogen recognition, and pattern recognition receptors (PRRs) are necessary for this process to occur. Toll-like receptor (TLR) 2 plays a critical role in recognition of the conserved portion of Gram-positive bacteria [2], and it is known that mastitis can increase expression of the TLR2 gene in mammary glands [3]. Genetic diversity in the TLR2 gene is a risk factor for staphylococcus infection [4], and TLR2−/− mice are susceptible to S. aureus [5].…”
Section: Introductionmentioning
confidence: 99%